Initial SARS-CoV-2 vaccination response can predict booster response for BNT162b2 but not for AZD1222. (September 2021) - Perkmann, Thomas; Perkmann-Nagele, Nicole; Mucher, Patrick; Radakovics, Astrid; Repl, Manuela; Koller, Thomas; Jordakieva, Galateja; Wagner, Oswald F.; Binder, Christoph J.; Haslacher, Helmuth
ABSTRACT: Objective: To determine whether severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) antibody levels after the first dose of vaccine can predict the final antibody response, and whether this is dependent on the vaccine type. Methods: Sixty-nine recipients of BNT162b2 (Pfizer/BioNTech) and 55 recipients of AZD1222 (AstraZeneca), without previous infection or immunosuppressive medication, were included in this study. Antibody levels were quantified 3 weeks after the first dose [directly before boostering in the case of AZD1222 (11 weeks after the first dose)] and 3 weeks after the second dose using the Roche Elecsys SARS-CoV-2 S total antibody assay. Results: Median pre-booster {BNT162b2: 80.6 [interquartile range (IQR) 25.5–167.0] binding antibody units (BAU)/mL; AZD1222: 56.4 (IQR 36.4–104.8) BAU/mL; not significant} and post-booster [BNT162b2: 2092.0 (IQR 1216.3–4431.8) BAU/mL; AZD1222: 957.0 (IQR 684.5–1684.8) BAU/mL; P <0.0001] levels correlated well in the recipients of BNT162b2 (ρ=0.53) but not in the recipients of AZD1222. Moreover, antibody levels after the first dose of BNT162b2 correlated inversely with age (ρ=-0.33, P =0.013), whereas a positive correlation with age was observed after the second dose in recipients of AZD1222 (ρ=0.26, P =0.030). Conclusions: The results of this study suggest that antibody levels quantified by the Roche Elecsys SARS-CoV-2 S assay before the booster shot could infer post-booster responses to BNT162b2, but not to AZ1222. In addition, this study found a vaccine-dependent effect on antibody responses, where age seems to play an ambivalent role.